(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the possibilities of using modern geographic information systems (GIS) technologies in assessing air quality in Uzbekistan on a scientific basis. The study studied air pollution indicators (NO₂, CO, PM2.5) for January-June 2025 based on data from the Sentinel-5P satellite, the Copernicus Atmospheric Monitoring Service, the OpenAQ platform, and the Google Earth Engine system. The results showed that the highest levels of air pollution are observed in the cities of Tashkent, Navoi, Angren, and Fergana. The article highlights the practical importance of GIS technologies in environmental analysis, forecasting, and management.